A dislocation-based stress-strain gradient plasticity model for strength and ductility in materials with gradient microstructures. Issue 32 (12th November 2018) - Hamid, Mehdi; Lyu, Hao; Zbib, Hussein
ABSTRACT: Although metallic materials with gradient microstructure exhibit notable performance in harsh environmental conditions, they can also exhibit unusual mechanical behaviour. This is attributed to both grain size and the gradient of grain size distribution in the structure. Metallic materials with a homogenous distribution of grain size follow the traditional Hall-Petch relationship, in which strength increases with decreasing grain size at the expense of ductility. However, studies show that materials with a gradient of grain size microstructure do not follow the Hall-Petch relationship, and thus have improved strength and ductility. This suggests that with creative design and engineering of microstructure, the strength-ductility trade-off can be reduced or prevented. In this study, we developed and implemented a dislocation density based model to investigate the mechanical behaviour of nano-microstructure. We designed a multi-scale modelling framework, coupling VPSC (Viscoplastic Self Consistent model) with CDD (Continuum Dislocation Dynamics), applying crystal plasticity equations to simulate dislocation interaction in polycrystalline metallic materials. We also developed design parameters and a model to predict the strength and ductility of materials with gradient microstructure.